2022
DOI: 10.3389/fped.2022.830587
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Features of PCR-Confirmed and Clinically Suspected COVID-19 Pediatric Patients: A Single Hospital-Based Experience During the First COVID-19 Wave in the United Arab Emirates

Abstract: ObjectiveThis study investigated clinical and laboratory differences between confirmed (RT-PCR-positive) and clinically suspected (RT-PCR-negative) COVID-19 pediatric patients, and explored factors associated with disease severity at presentation and duration of hospitalization.MethodsMedical charts of COVID-19-confirmed and clinically suspected pediatric patients admitted to a tertiary hospital in Abu Dhabi were reviewed. Sociodemographic information and clinical and laboratory outcomes were retrieved and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…C-reactive protein was higher in clinically suspected compared to confirmed patients. Lymphocyte, Lactate Dehydrogenase (LDH), D-dimer, ferritin levels after 24-36 hours, and Serum Glutamic Pyruvic Transaminase (SGPT) were associated with disease severity [9]. Also, a study that included over 10,000 hospitalized children found that abnormal markers of inflammation, including D-dimers and ferritin, were associated with severe disease in children [3].…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…C-reactive protein was higher in clinically suspected compared to confirmed patients. Lymphocyte, Lactate Dehydrogenase (LDH), D-dimer, ferritin levels after 24-36 hours, and Serum Glutamic Pyruvic Transaminase (SGPT) were associated with disease severity [9]. Also, a study that included over 10,000 hospitalized children found that abnormal markers of inflammation, including D-dimers and ferritin, were associated with severe disease in children [3].…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…C-reactive protein was higher in clinically suspected compared to confirmed patients. Lymphocyte, Lactate Dehydrogenase (LDH), D-dimer, ferritin levels after 24-36 hours, and Serum Glutamic Pyruvic Transaminase (SGPT) were associated with disease severity [9]. Also, a study that included over 10,000 hospitalized children found that abnormal markers of inflammation, including D-dimers and ferritin, were associated with severe disease in children [3].…”
Section: Laboratory Findingsmentioning
confidence: 99%